Financial Disadvantage and Children's School readiness - Baxter, Jennifer; Smart, Diana; Edwards, Ben; Sanson, Ann; Hayes, Alan (My University, 2009)
The transition from home to school is a major change in children's lives. Children vary in their 'readiness' for this transition, and the marked differences visible in children's cognitive and social and emotional skills at school entry have implications for later outcomes. In this paper, the authors examine the impact of living in financial disadvantage on children's school readiness and the role that other risk and protective factors play, drawing upon data from Growing Up in Australia, the Longitudinal Study of Australian Children. The first section of this paper provides a short summary of the research literature and describes two theoretical models that seek to explain why financial disadvantage is related to school readiness. The authors then present evidence of a consistent association between low income and the cognitive and learning components of children's school readiness at 4?5 years of age. A wide range of risk and protective factors associated with school readiness are identified, including child and parental characteristics, parenting style, the family educational climate, early education and care, and neighbourhood characteristics. These risk and protective factors are also likely to underpin the links between financial disadvantage and school readiness.
Family Matters
Keywords: Education and Training; Education and Training -- Earlychildhood; Finance -- Poverty and Disadvantage; Children; Finance; Income, wealth and finances; Learning, education and training; Finance; Education and Training; Children; Poverty and Disadvantage; Earlychildhood; Learning, education and training; Income, wealth and finance